Exploring visitors' experience using strategic experiential modules (SEMs): the case of Zoo Negara, Kuala Lumpur. Issue 3 (10th August 2015) - Musa, Ghazali; Mohammad, Izzah; Thirumoorthi, Thinaranjeney; Moghavvemi, Sedigheh; Kasim, Azilah
Abstract : Purpose: – The purpose of this paper is to explore the experiences of visitors using the strategic experiential modules (SEMs). Design/methodology/approach: – In this study, the authors analysed a total of 37 essays written by University of Malaya students who visited the attraction on 23 November 2013. The aim is to explore what constitutes the elements within the SEMs, pertaining to the students' visit. The results are potentially useful for future Zoo Negara marketing communication initiatives, as well as for the management to remedy the shortfalls which have hindered Zoo Negara from operating as a self-sustaining attraction. Findings: – The results confirmed the applicability of all five dimensions of the modules, which include both positive and negative elements. Of the five dimensions, THINK and SENSE were the most frequently expressed. Originality/value: – Though this study offers no theoretical contribution, it does demonstrate the applicability of the Schmitt theory on SEMs and the usefulness of such an application from the managerial perspective.